Determinants of voluntary adoption of Sustainability Accounting Standards Board standards to disclose sustainability issues: an international perspective - Lopes, A.I.; Carvalho, A.R. (VIII International Forum on Management, 2024)
The purpose of this research is to investigate the impact of company- and country specific variables on voluntary adoption of the Sustainability Accounting Standards Board (SASB) Standards in organizations that publish Integrated Reports (IR) and simultaneously use GRI standards to disclose ESG practices. It is based on an international sample of 8,247 firm-year observations between 2019 and 2021, where 6,856 used GRI standards and the remaining 1,391 used both SASB and GRI standards. The findings indicate that business characteristics such as large size, profitability, leverage, ESG score, board size, independent directors, and specific abilities are relevant determinants. Firms who conformed to the IR and use GRI are more likely to simultaneously adopt SASB Standards voluntarily if they are located in nations with a higher GDP (Gross Domestic Product) per capita. Furthermore, the findings show that larger market-to-book ratios, gender diversity on the board, and the number of non-executive members on the board had low effect on the adoption of SASB Standards by firms that have already adhered to the IR.